2017
DOI: 10.1584/jpestics.d16-104
|View full text |Cite
|
Sign up to set email alerts
|

Insect TRP channels as targets for insecticides and repellents

Abstract: This review provides a brief overview of ion channels, then focuses on TRP channels, describing the properties and functions of the seven TRP channel classes found in insects. Finally, recent work showing that a heteromeric channel composed of Nanchung and Inactive vanilloid TRP (TRPV) channel subunits is the target of the selective feeding blockers pymetrozine and pyrifluquinazon is described. The possible utility of other TRP channels as targets of insecticides and repellents is also considered. © Pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 59 publications
(81 reference statements)
1
27
0
Order By: Relevance
“…Remarkably, the repellency of CDIAL was comparable to DEET—the current gold standard for a repellent—despite an over 1.5-times lower molar amount of CDIAL vs. DEET used in the assays. Thus, our findings galvanize the notion suggested by others that TRPA1 agonists offer valuable potential molecules for the development of new repellents [ 31 , 34 , 40 43 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Remarkably, the repellency of CDIAL was comparable to DEET—the current gold standard for a repellent—despite an over 1.5-times lower molar amount of CDIAL vs. DEET used in the assays. Thus, our findings galvanize the notion suggested by others that TRPA1 agonists offer valuable potential molecules for the development of new repellents [ 31 , 34 , 40 43 ].…”
Section: Discussionsupporting
confidence: 84%
“…Emerging evidence in vertebrate and insect systems (including mosquitoes) suggests that electrophilic unsaturated sesquiterpene dialdehydes are agonists of Transient Receptor Potential A1 (TRPA1) channels, which are receptors that play important roles in the environmental sensing and avoidance of potentially noxious chemicals, as well as temperatures [ 31 39 ]. Chemical agonists of TRPA1 have been suggested as potential molecules for the development of new insect repellents [ 31 , 34 , 40 43 ]. Thus, we also tested the hypothesis that CDIAL’s mechanism of action in mosquitoes involved the modulation of TRPA1.…”
Section: Introductionmentioning
confidence: 99%
“…Application of the insecticide pymetrozine on the female's genitalia reduced the mechanosensory responses to tap stimulation. Pymetrozine is a pesticide that interferes with a subgroup of insect transient receptor potential channels [37,38], selectively blocking chordotonal receptors [30]. We therefore assume that besides mechanosensilla on the surface the titillator taps are also perceived by proposed internal chordotonal receptors of the female's genital fold [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have shown that both pymetrozine and afidopyropen act by modulating TRPV channels [ 15 , 16 ], and that TRPA1 in the mosquito vector for malaria, Anopheles gambiae , is potently and directly activated by citronellal [ 17 ]. Thus, TRPs have become potential targets for insecticide development as well as for improved repellents to control insect-borne diseases [ 18 , 19 ]. Investigating the molecular characteristics of TRPs in B. dorsalis will enable a better understanding of this system in a key agricultural pest and will provide a firm foundation for future insecticide design targeting these channels.…”
Section: Introductionmentioning
confidence: 99%